Communication in Vertically Related Markets: Experimental Evidence - Hans-Theo Normann; Claudia Möllers; Christopher M. Snyder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
When an upstream monopolist supplies several competing downstream firms, it may fail to monopolize the market because of opportunistic behavior towards the downstream firms. We analyze this well-known commitment problem in an experiment where we extend previous research by allowing for communication. In one treatment, the upstream firm can bilaterally talk to either of two downstream firms. In a second treatment, all three firms talk together. We find that the treatment with bilateral communication leads to fewer rejections of offers and higher joint profits than a baseline treatment without communication, but output is still above the monopoly benchmark. Only the treatment where all three firms can communicate leads to complete monopolization. Such communication effectively works as a vertical restraint and should be regarding as potentially anticompetitive.
Keywords: L12; L42; C90; 330